2013
DOI: 10.1037/a0028988
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the acquired preparedness model: The effects of impulsivity and expectancies on smoking initiation in college students.

Abstract: Aims This paper reports on a prospective test of the Acquired Preparedness Model, which posits that impulsivity influences cigarette smoking through the formation of more positive and fewer negative expectancies about smoking effects. Design College freshman never-smokers (n = 400; 45% male) completed a baseline interview and quarterly online follow-up assessments for 15 months following baseline. Findings Structural equation modeling indicated that the effects of the impulsivity components of sensation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 76 publications
(119 reference statements)
5
74
2
2
Order By: Relevance
“…Specifically, the full mediational model that included impulsivity and outcome expectancies robustly predicted both frequency and gambling symptomatology. In addition, this study provided further support for a multidimensional measurement of impulsivity (e.g., Dir, Cyders & Coskunpinar, 2013; Doran et al, 2012; Schaumberg & Earleywine, 2013). In this case, we found that three gambling specific impulsivity dimensions were each related to gambling activity and symptomology, and these relations were uniquely mediated by different gambling outcome expectancies.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Specifically, the full mediational model that included impulsivity and outcome expectancies robustly predicted both frequency and gambling symptomatology. In addition, this study provided further support for a multidimensional measurement of impulsivity (e.g., Dir, Cyders & Coskunpinar, 2013; Doran et al, 2012; Schaumberg & Earleywine, 2013). In this case, we found that three gambling specific impulsivity dimensions were each related to gambling activity and symptomology, and these relations were uniquely mediated by different gambling outcome expectancies.…”
Section: Discussionsupporting
confidence: 57%
“…This bias, in turn, influences a person's outcome expectancies and ultimately the engagement in the risk taking behavior. Studies on various risk behaviors by college students have provided support for this model (e.g., Doran et al, 2012; McCarthy, Kroll, & Smith, 2001; Vangsness, Bry, Erich & Labouvie, 2005), but have not tested the model with gambling. The purpose of this study was to examine whether the acquired preparedness model can be used to evaluate the relation between three impulsivity dimensions and more proximal risk factors of outcome expectancies on gambling involvement and problematic gambling risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of sensation seeking in relation to subsequent smoking has been much less studied (Crawford, Pentz, Chou, Li, & Dwyer, 2003). Explanatory mechanisms for the association between sensation seeking and the initiation of smoking include heightened reward sensitivity to nicotine, underestimation of risk, consorting with other sensation-seeking peers, and expectancies for positive reinforcement from smoking (Doran et al, 2012;Perkins et al, 2008;Wills, Windle, & Cleary, 1998;Yanovitzky, 2005).…”
Section: Sensation Seeking As An Etiological Variablementioning
confidence: 99%
“…Initial studies addressing this issue found that approximately 11% of college students smoked their fi rst cigarette after age 18 or following college enrollment (Everett et al, 1999;Wechsler et al, 1998;Wetter et al, 2004). More recent prospective research suggests substantially higher smoking initiation during the college years, with 18%-25% of students who had not previously smoked reporting cigarette smoking within their fi rst 2 years in college (Costa et al, 2007;Doran et al, 2012;Tercyak et al, 2007). Substantial initiation also appears to occur among students from ethnic groups with low smoking rates, as suggested by a longitudinal study of Asian American college students in which 25% of those who had not smoked before entering college initiated smoking before the end of their fourth year in college (Myers et al, 2009).…”
mentioning
confidence: 99%